Edge Effects in Tree Diversity and Carbon Stock in South Slope at Phulchoki Forest, Lalitpur Nepal - Dhakal, Sagar; Singh, Manoj Kumar; Kandel, Hari; Lalkarn, Lalbabu (Amrit Research Journal, 2023)
The floral community changes in elevation. Due to the more diverse ecological characteristics, the diverse flora, and the number of landscape elements, there is a change in diversity called the edge effect. This study examines the role of altitude (1400–1800 m, 1800–2400 m, and above 2400 m) and how floral diversity changes with altitude variation. The aim of this study is to examine the carbon stock at which altitudinal range it is higher and why. One tree species (oak) was found at highest altitude (2650 m) followed by intermediate altitude (2100 m) further with greatest number of tree species at low altitude (1600 m). Higher species diversity (Shanon Index: 2.1863) and density (5575 individuals per hectares) was found at altitudinal range I (1400 to 1800 m) composed by Rhododendrum arborium, Quercus glauca, Myrica esculenta, and Myrsine capitellat. Whereas Rhododendron arboretum, Castanopsis tribuloides, and Quercus incana dominate altitudinal range II (1800m to 2400m) with diversity (Shannon Index: 1.759) and an average density (2150 individuals per hectare). In Altitudinal Area III (2400 m and above), the forest is dominated by Quercus semicarpifolia. The highest carbon stock was found in the altitudinal range (1800m to 2400m) compared to altitudinal ranges I and III. Edge effects shaped the community composition and affected tree diversity and carbon stock. In conclusion, the floral community and carbon stock were affected by forest edges, which led to conservation actions and mitigation of climate change in surprisingly different ways.